PENGARUH PEMBELAJARAN ZEP QUIZ BERBASIS PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR BIOLOGI KELAS IX SMP - Afif Amalia; Jailani Jailani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Zep quiz is a digital application designed to create interest and learning outcomes. Students will be more motivated, more focused, and find it easier to understand the material when learning is designed in the form of an educational quiz game. This study aims to find out the differences in learning outcomes of students who follow learning with the interactive zep quiz media based on Problem Based Learning compared to students who learn without using the media. It also aims to find out the extent of the influence of interactive learning media Zep quiz based on Problem Based Learning on the improvement of students' learning outcomes in biology subjects for class IX at SMP Muhammadiyah 5 Samarinda. The type of research used is quasi-experiment. Data collection techniques were carried out through interviews and observations, tests, and documentation. Based on the data analysis results obtained, the significance value (sig. 2-tailed) is 0.189 > 0.05, so Ho is accepted and Ha is rejected. In addition, the calculated t value is 1.335 < t table 2.018, so Ho is accepted and Ha is rejected. This indicates that there is no significant difference between the learning outcomes of the experimental class and the control class. Thus, it can be concluded that the use of interactive learning media Zep Quiz based on Problem Based Learning does not have a significant effect on students' learning outcomes in the biology subject of class IX at SMP Muhammadiyah 5 Samarinda. ABSTRAK Zep quiz adalah aplikasi digital yang dirancang untuk menciptakan minat dan hasil belajar. Siswa akan lebih termotivasi, lebih fokus dan lebih mudah untuk memahami materi ketika pembelajaran yang dirancang dalam bentuk permainan quiz yang edukatif. Penelitian ini bertujuan mengatahui perbedaan hasil belajar siswa yang mengikuti pembelajaran dengan media interaktif zeep quiz berbasis Problem Based Learning dengan siswa yang belajar tanpa menggunakan media tersebut. Mengeatahui sejauh mana pengaruh media pembelajaran interaktif zeep quiz berbasis Problem Based Learning terhadap peningkatan hasil belajar siswa pada mata pelajaran biologi kelas IX SMP Muhammadiyah 5 Samarinda. Jenis penelitian yang digunakan yaitu quasi experiment. Teknik pengumpulan data dilakukan melalui wawancara dan observasi, tes serta dokumentasi. Berdasarkan hasil analisis data yang diperoleh nilai signifikansi (sig. 2-tailed) sebesar 0,189 > 0,05, sehingga Ho diterima dan Ha ditolak. Selain itu diperoleh nilai t hitung 1,335 < t tabel 2,018, sehinggaHo diterima dan Ha ditolak. Hal ini menunjukkan bahwa tidak terdapat perbedaan yang signifikan antara hasil belajar kelas eksperimen dan kelas kontrol. Dengan demikian dapat disimpulkan bahwa penggunaan media pembelajaran interaktif zep quiz berbesis Problem Based Learning tidak memberikan pengaruh yang signifikan terhadap hasil belajar siswa pada mata pelajaran biologi kelas IX SMP Muhammadiyah 5 Samarinda